1984
DOI: 10.1038/312763a0
|View full text |Cite
|
Sign up to set email alerts
|

The CD4 (T4) antigen is an essential component of the receptor for the AIDS retrovirus

Abstract: Acquired immune deficiency syndrome (AIDS) is characterized by opportunistic infections and by 'opportunistic neoplasms' (for example, Kaposi's sarcoma). Persistent generalized lymphadenopathy (PGL) is epidemiologically associated with AIDS, especially in male homosexuals. A subset of T lymphocytes positive for the CD4 antigen (also termed T4 antigen), is depleted in AIDS and PGL patients. A retrovirus found in T-cell cultures from these patients is strongly implicated in the aetiology of AIDS because of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
1,508
2
23

Year Published

1986
1986
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,233 publications
(1,548 citation statements)
references
References 31 publications
15
1,508
2
23
Order By: Relevance
“…Although speculative, the function of VCBPs might be to recognize determinants on various pathogens. There is considerable precedent for IgSF-related viral receptors, including those for poliovirus (poliovirus receptor) 116 , reovirus (junctional adhesion molecule, JAM) 117 , HIV (CD4) 118 , mouse hepatitis virus (CEA-related cell-adhesion molecule 1, CEACAM1) 119 , measles virus (signalling lymphocytic activation molecule, SLAM) 120 and others. Other potential functions for VCBPs include binding to fungal or bacterial surfaces, direct opsonization, and self-and non-self-recognition 3,7 .…”
Section: Vcbps In Protochordatesmentioning
confidence: 99%
“…Although speculative, the function of VCBPs might be to recognize determinants on various pathogens. There is considerable precedent for IgSF-related viral receptors, including those for poliovirus (poliovirus receptor) 116 , reovirus (junctional adhesion molecule, JAM) 117 , HIV (CD4) 118 , mouse hepatitis virus (CEA-related cell-adhesion molecule 1, CEACAM1) 119 , measles virus (signalling lymphocytic activation molecule, SLAM) 120 and others. Other potential functions for VCBPs include binding to fungal or bacterial surfaces, direct opsonization, and self-and non-self-recognition 3,7 .…”
Section: Vcbps In Protochordatesmentioning
confidence: 99%
“…The human immunode®ciency virus (HIV), the agent etiologically related to the acquired immunode®ciency syndrome (AIDS) (Barre-Sinoussi et al, 1983), preferentially infects helper inducer T lymphocytes (Dalgleish et al, 1984). Termination of the long latency of AIDS in patients infected with HIV-1 is marked by a profound depletion of CD4 + T cells and the decline of HIV-1 speci®c cytotoxic CD8 + T cells (Meyaard et al, 1992(Meyaard et al, ,1994.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from our laboratory has shown that oxidative stress produced by hydrogen peroxide can induce the reactivation of latent HIV-1 [20]. This virus predominantly infects T-helper cells, macrophages and monocytes [21]. Following penetration of these cells, its genome becomes integrated in cell chromosomes and the provirus can remain latent for several years.…”
Section: Introductionmentioning
confidence: 99%